Microsoft Vista for IT security professionals - Piltzecker, Tony, 1975-; Chaffin, Larry (Syngress Publishing, 2007)
This book is designed for the professional system administrators who need to securely deploy Microsoft Vista in their networks. Readers will not only learn about the new security features of Vista, but they will learn how to safely integrate Vista with their existing wired and wireless network infrastructure and safely deploy with their existing applications and databases. The book begins with a discussion of Microsoft's Trustworthy Computing Initiative and Vista's development cycle, which was like none other in Microsoft's history. Expert authors will separate the hype from the reality of Vistas preparedness to withstand the 24 x 7 attacks it will face from malicious attackers as the worlds #1 desktop operating system. The book has a companion CD which contains hundreds of working scripts and utilities to help administrators secure their environments. Microsoft Windows operating systems run more than 90% of the desktop PCs in the world and Vista is the first major Windows release in more than 5 years This is currently the only book on Windows Vista Security The companion CD contains hundreds of working scripts and utilities to help administrators secure their environments.